Microorganisms from N95 masks were reused for 36h and then decontaminated by heat which we learned from the COVID-19 pandemic (Research, Society and Development, 2022)
The aim of this study is to analyze the Microorganisms of N95 masks reused for 36 hours and after heat decontamination. Methodology: Experimental study with a sample of 12 N95 masks reused by professionals in the contaminated area of a material and sterilization center for 36 hours, and after decontamination by heat, where two means of decontamination were applied, the thermo-disinfection by moist heat (90ºC) and dry heat (70ºC) in the cabinet dryer, for 1h of exposure, then seeded in chocolate agar culture medium and incubated 48h in a biological incubator at 37ºC. Results: Before decontamination, there was the development of non-pathogenic microorganisms from the resident flora of the mouth, nose, and skin: gran+ cocci, Bacillus gran-Candida Spp, Staphylococcus, and Streptococcus, between 2 to 8 Colony-forming units (CFU). After decontamination, there was no development of microorganisms. As to the macroscopic aspect, those submitted to thermodisinfection suffered visible structural damage, and tears, preventing reuse, while those submitted to dry heat were intact and in reusable condition, as required by the Centers for Disease Control and Prevention (CDC), regarding the sealing test and adjustment to the face. Conclusion: Considering that many routines established during the COVID-19 pandemic will remain, such as the reuse of N95 masks, solutions need to be found for comfortable use while protecting workers. The method, using dry heat, is a viable, fast and simple alternative to decontaminating N95 masks.